26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0265
|View full text |Cite
|
Sign up to set email alerts
|

Kaizen - Analysis of the Implementation of the A3 Reporting Tool in a Steel Structure Company

Abstract: The A3 report is a Kaizen tool that must contain, on one side of an A3 paper sheet, a context, the current situation, the objective, an analysis, countermeasures, an action plan, the monitoring and an upgrade regarding the situation to be improved. This study seeks to analyze the post-implementation effects of the A3 tool, which is part of the Kaizen method. The research method consisted in the collection and evaluation of A3 reports produced in the past seven years in a company of prefabricated steel structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Addressing the root causes of the problem has the added advantage of avoiding a re-occurrence of same problem. Bordin et al (2018) showed from a case study that the A3 report was effective in the deployment of continuous improvement initiatives, resulting in the improvement of services and processes, and consequently in the direct reduction of the cost of the finished product. A3 reports also improve transparency.…”
Section: Status Of Lean Constructionmentioning
confidence: 99%
“…Addressing the root causes of the problem has the added advantage of avoiding a re-occurrence of same problem. Bordin et al (2018) showed from a case study that the A3 report was effective in the deployment of continuous improvement initiatives, resulting in the improvement of services and processes, and consequently in the direct reduction of the cost of the finished product. A3 reports also improve transparency.…”
Section: Status Of Lean Constructionmentioning
confidence: 99%
“…A3 report. The A3 report has been widely used in the implementation of lean production to serve as a tool to support the improvement processes, which is based on the PDCA system management method, promoting the interaction and integration of all people and areas involved in the problem or situation to be enhanced (Bordin et al, 2018). Furthermore, the author points out that the A3 report implies a significant questioning of the importance of addressing the problem for the organization and clearly establishing the current context as a basis for defining objectives, conducting a root cause analysis, generating countermeasures, developing an action plan and monitoring and controlling the results.…”
Section: Agile Design Management (Adm)mentioning
confidence: 99%
“…The values that have become habits are called culture. Because culture is associated with the quality or quality of work (Bordin et al, 2018).…”
Section: Kaizenmentioning
confidence: 99%